Artificial Intelligence- Legal Issues And Challenges - Dave, Tuhina; Menezes, Riea (Trinity Law Review, 2022)
This paper intends to provide insights on the race of our traditional law against the ever-evolving and fast-paced technology. It is important to dive a little deeper to understand the density and ambiguity revolving around the increased use of AI. This paper highlights the impacts of AI under the lens of ethics and law, intending to discuss, explore and understand the implications. The challenges related to AI are witnessed not only in the field of the law but also affect the rights granted to individuals under the law and the same has been captured in this paper which is based on extensive research and recent events.The need of the hour is not a definitive answer or a concrete solution but to lay a strong foundation in our legal system for the unforeseeable challenges that may come our way.